2017
DOI: 10.3389/fmicb.2017.00749
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, Intestinal Transport, and Bioavailability of Dispersible Iron and Zinc Supplements

Abstract: Iron or zinc deficiency is one of the most important nutritional disorders which causes health problem. However, food fortification with minerals often induces unacceptable organoleptic changes during preparation process and storage, has low bioavailability and solubility, and is expensive. Nanotechnology surface modification to obtain novel characteristics can be a useful tool to overcome these problems. In this study, the efficacy and potential toxicity of dispersible Fe or Zn supplement coated in dextrin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
1
4
0
3
Order By: Relevance
“…M cells found in Peyer’s patches in the small intestine are implicated in the transport of various molecules, including macromolecules and particles [ 43 , 44 ]. Indeed, the intestinal transportation of diverse NPs by M cells has been recently reported [ 45 , 46 , 47 ], which concurs with our results. It should be noted that ZnO particles can be also transported through intestinal tight junction barriers, as demonstrated by our Caco-2 monolayer model.…”
Section: Discussionsupporting
confidence: 94%
“…M cells found in Peyer’s patches in the small intestine are implicated in the transport of various molecules, including macromolecules and particles [ 43 , 44 ]. Indeed, the intestinal transportation of diverse NPs by M cells has been recently reported [ 45 , 46 , 47 ], which concurs with our results. It should be noted that ZnO particles can be also transported through intestinal tight junction barriers, as demonstrated by our Caco-2 monolayer model.…”
Section: Discussionsupporting
confidence: 94%
“…Previous in vitro studies suggested that gastrointestinal uptake of iron NPs could occur through several mechanisms 13 , 26 , 27 . Our in vivo data suggest that absorption of FePO 4 -NPs is largely DMT1 dependent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados del experimento en Artemia salina, arrojaron valores prácticamente nulos de mortalidad para las muestras de M y cM en todo el rango de concentraciones estudiado (Figura IIB3). Ésto es consistente con la información publicada para NP de pirofosfato férrico (FePP) que no presentaron citotoxicidad al ser evaluadas en células intestinales humanas INT-407 y Caco-2 (Kim et al, 2017).…”
Section: Iib3 Resultados Y Discusiónunclassified
“…Considerando que los beneficios del consumo de probióticos pueden ser obtenidos cuando se administran en concentraciones de al menos 7 log UFC de microorganismos viables por gramo de producto (Kim et al, 2017), los valores obtenidos tanto luego de la digestión como después de 60 días de almacenamiento garantizan la ingestión de las cantidades requeridas. Como la pectina forma parte de la fibra dietaria, la ingesta de las NP con pectina facilitaría su llegada al intestino ya que las pectinas no serían hidrolizadas en el tracto gastro-intestinal superior (Figura IIA12).…”
Section: Iia324 Viabilidad Bacteriana Durante La Digestión In Vitunclassified
See 1 more Smart Citation